KUALITAS HIDUP PASIEN KANKER PAYUDARA DI RUANG EDELWEIS RSUD ULIN BANJARMASIN - Erna Prihandiwati; Melia Digna Pratiwi; Noverda Ayuchecaria; Novia Ariani; Noor Aisyah; Mardiana Mardiana (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2019)
Breast cancer is the biggest problem for women around the world and causes a major death for patients with breast cancer. Breast cancer and its treatment or side effects of treatment are often associated with a decrease in the quality of life of breast cancer patients. In Indonesia, the prevalence of cancer / tumor is quite high at 1.4 per 1000 population, or about 330,000 people. The purpose of this study was to determine the quality of life of breast cancer patients in the edelweiss room of Ulin Banjarmasin Public Hospital. This research is a descriptive non-experimental research. The study was conducted at Ulin Banjarmasin Hospital in the period of July-August 2018. The sampling method used was consecutive sampling. The study population was 85 breast cancer patients and the study sample was all of the population because the entire population met the inclusion criteria. The instrument used was the European Quality Of Life - 5 Dimension questionnaire and the EQ-5D Index Calculator by using the Japanese state to calculate the score for each item of question on the EQ-5D-3L questionnaire. The result of this research is the description of the quality of life in 85 research respondents as much as 57.7% had a good quality of life and as much as 42.3% had poor quality of life.